Determinan Kinerja Kewirausahaan Sosial Berkelanjutan - Ajis Purnomo; Erny Tajib; Maria Ariesta Utha (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the determinants of sustainable social entrepreneurship performance through the influence of local hero leadership, mediated by knowledgeable human resources, network capability, and digital innovation, and moderated by collaborative energy. A quantitative approach was used with purposive sampling method. Data were collected from 202 respondents across 14 MSMEs located in South Sumatra, Lampung, and West Sumatra using a Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM). The results show that local hero leadership positively influences the three mediating variables in enhancing sustainable social entrepreneurship performance. However, collaborative energy did not show a significant moderating effect on human resources and network capability, and even had a negative impact on digital innovation. These findings indicate that not all forms of collaboration support innovation. The practical implication is that the significant variables in this study can be used as Key Performance Indicators (KPI) for empowerment programs based on social entrepreneurship and the Sustainable Development Goals (SDGs). It also highlights the importance of maintaining the role of local heroes and designing digital strategies that are adaptive to organizational needs.